Mental health and wellbeing during the transition to fatherhood: a systematic review of first time fathers' experiences. (November 2018) - Baldwin, Sharin; Malone, Mary; Sandall, Jane; Bick, Debra
ABSTRACT: Objective: The aim of this systematic review was to identify and synthesize the best available evidence on first time fathers' experiences and needs in relation to their mental health and wellbeing during their transition to fatherhood. Introduction: Men's mental health and wellbeing during their transition to fatherhood is an important public health issue that is currently under-researched from a qualitative perspective and poorly understood. Inclusion criteria: Resident first time fathers (biological and non-biological) of healthy babies born with no identified terminal or long-term conditions were included. The phenomena of interest were their experiences and needs in relation to mental health and wellbeing during their transition to fatherhood, from commencement of pregnancy until one year after birth. Studies based on qualitative data, including, but not limited to, designs within phenomenology, grounded theory, ethnography and action research were included. Methods: A three-step search strategy was used. The search strategy explored published and unpublished qualitative studies from 1960 to September 2017. All included studies were assessed by two independent reviewers and any disagreements were resolved by consensus or with a third reviewer. The recommended Joanna Briggs Institute (JBI) approach to critical appraisal, study selection, data extraction and data synthesis was used. Results: Twenty-two studies met the eligibility criteria and were included in the review, which were then assessed to be of moderate to high quality (scores 5–10) based on the JBI Critical Appraisal Checklist for Qualitative Research. The studies were published between 1990 and 2017, and all used qualitative methodologies to accomplish the overall aim of investigating the experiences of expectant or new fathers. Nine studies were from the UK, three from Sweden, three from Australia, two from Canada, two from the USA, one from Japan, one from Taiwan and one from Singapore. The total number of first time fathers included in the studies was 351. One hundred and forty-four findings were extracted from the included studies. Of these, 142 supported findings were aggregated into 23 categories and seven synthesized findings: 1) New fatherhood identity, 2) Competing challenges of new fatherhood, 3) Negative feelings and fears, 4) Stress and coping, 5) Lack of support, 6) What new fathers want, and 7) Positive aspects of fatherhood. Conclusions: Based on the synthesized findings, three main factors that affect first time fathers' mental health and wellbeing during their transition to fatherhood were identified: the formation of the fatherhood identity, competing challenges of the new fatherhood role and negative feelings and fears relating to it. The role restrictions and changes in lifestyle often resulted in feelings of stress, for which fathers used denial or escape activities, such as smoking, working longer hours or listening to music, as coping techniques. Fathers wanted more guidance and support around the preparation for fatherhood, and partner relationship changes. Barriers to accessing support included lack of tailored information resources and acknowledgment from health professionals. Better preparation for fatherhood, and support for couple relationships during the transition to parenthood could facilitate better experiences for new fathers, and contribute to better adjustments and mental wellbeing in new fathers.